Which expression is equivalent to the equation above
![Which expression is equivalent to the equation above class=](https://us-static.z-dn.net/files/db5/76cbcf59e7c1553b9876beb778e82617.jpeg)
Answer: third option
Step-by-step explanation:
The negative exponent rules establishes:
[tex]a^{-n}=\frac{1}{a^n}[/tex]
The power to power property establishes:
[tex](a^b)^c=a^{bc}[/tex]
The quotien of power property establishes that when you divide two powers with equal base you must subtract the exponents.
Applying the properties, you obtain:
[tex]\frac{(4p^{-4}q)^{-2}}{10pq^{-3}}}=\frac{q^3}{10(4p^{-4}q)^{2}}=\frac{q^3}{10p(16p^{-8}q^{2})}=\frac{p^8q^3}{160pq^2}=\frac{p^7q}{160}[/tex]
Answer:
The correct answer is third option
p⁷q/160
Step-by-step explanation:
Points to remember
1). ( xᵃ)ᵇ = xᵇ
2). x⁻ᵃ = 1/xᵃ
It is given that, (4p⁻⁴q)⁻²/10pq⁻³
To find the equivalent of (4p⁻⁴q)⁻²
(4p⁻⁴q)⁻² = 4⁻²p⁸q⁻²
= p⁸/4²q²
= p⁸/16q²
To find the equivalent of 10pq⁻³
1/10pq⁻³ = q³/10p
To find the equivalent of (4p⁻⁴q)⁻²/10pq⁻³
(4p⁻⁴q)⁻²/10pq⁻³ =p⁸q³/16q²10p = p⁷q/160
Therefore the correct answer is option 3